1979
DOI: 10.1111/j.1399-0039.1979.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Program for Anti‐DR Typing Reagents

Abstract: A total of 694 sera have been tested in a screening program aimed a t identifying monospecific reagents for HLA-DR typing. All sera were first tested on a panel of enriched B and T cells without absorption on platelets. Only sera reacting more frequently on B than on T lymphocytes were absorbed on platelets and retested on the panel. This procedure saved a considerable amount of platelets and proved to be reasonably efficient. One-hundred-and-fifty sera were found to contain an anti-B cell antibody. Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…By using quantitative microabsorption, Pellegrino et al (1978) have found that B lymphocytes express more HLA-AB antigens than T lymphocytes, although this difference was not found to be accompanied by greater susceptibility of the B cells to complement mediated lysis by HLA-AB antisera. Others, however, (Richiardi et al 1977, Vassalli et al 1979) have reported on cytotoxic sera reacting only with B cells, and not with T cells, with clearcut HLA-A or -B specificity. The present report demonstrates the possibility of B cell specific antisera even without discernible HLA-AB specificity giving occasional strong reactions which in fact are caused by HLA-AB antibodies, but mediated through synergistic action with HLA-DR components.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…By using quantitative microabsorption, Pellegrino et al (1978) have found that B lymphocytes express more HLA-AB antigens than T lymphocytes, although this difference was not found to be accompanied by greater susceptibility of the B cells to complement mediated lysis by HLA-AB antisera. Others, however, (Richiardi et al 1977, Vassalli et al 1979) have reported on cytotoxic sera reacting only with B cells, and not with T cells, with clearcut HLA-A or -B specificity. The present report demonstrates the possibility of B cell specific antisera even without discernible HLA-AB specificity giving occasional strong reactions which in fact are caused by HLA-AB antibodies, but mediated through synergistic action with HLA-DR components.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, synergism is also a factor of significance in HLA-DR serology which may explain unusual and actually "falsely positive" reactions. It is a common experience that HLA-DR test sera are often "contaminated" with HLA-ABC antibodies (Baricordi et al 1979, Vassalli et al 1979) and need absorption with platelets before use. Alternativcly, sera with weak HLA-ABC antibodies in addition to the HLA-DR component may be used without absorption if diluted properly out of detectable reactivity against T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, sera devoid of HLA-A,-B,-C antibodies are rarely strongly anti HLA-DR reactive (Baricordi et 0001-2815/82/060033-14 $ 02.5010 @ 1982Munksgaard, Copenhagen al. 1977, Moerloose et al 1977, Vassalli et al 1979, Muller et al 1980. This fact has 2 important implications.…”
mentioning
confidence: 99%
“…This fact has 2 important implications. Firstly, most sera containing HLA-DR antibodies have to be extensively absorbed with relevant platelets to remove HLA-A,-B,-C antibodies, and this in turn tends to weaken the anti HLA-DR reactivity, probably by non-specific absorption to the platelets (Vassalli et al 1979). Secondly, valuable HLA-DR antibodies may be overlooked in the screening procedure because of the simultaneous occurrence of HLA-A,-B,-C antibodies.…”
mentioning
confidence: 99%